2002
DOI: 10.1002/pip.431
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of an asymmetric static concentrator: the PEC‐44D

Abstract: In this paper, the optimisation of the PV static concentrator module PEC-44D for constant demand during the year is presented. The method used is based on simulation of the system performance during 10 years and the set of concentrator parameters that produces the lowest cost of the PV array is determined. We find that the optimised PEC-44D module can be 38% cheaper than a standard module. Experimental results were obtained for a prototype of the optimised PEC-44D to validate the theoretical analysis of the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Systems of a similar premise to this, with photovoltaic absorbers, have been discussed by a number researchers including: Brogren (2004), Brogren and Karlsson (2002), Gajbert et al (2007), Mallick et al (2004), Zacharopoulos et al (2000), Zanesco and Lorenzo (2002). However, in a recent study Piratheepan and Anderson (2013) compared the illumination profiles of a façade integrated collectors with parabolic and flat reflectors.…”
Section: Introductionmentioning
confidence: 92%
“…Systems of a similar premise to this, with photovoltaic absorbers, have been discussed by a number researchers including: Brogren (2004), Brogren and Karlsson (2002), Gajbert et al (2007), Mallick et al (2004), Zacharopoulos et al (2000), Zanesco and Lorenzo (2002). However, in a recent study Piratheepan and Anderson (2013) compared the illumination profiles of a façade integrated collectors with parabolic and flat reflectors.…”
Section: Introductionmentioning
confidence: 92%
“…The CPC is a nonimaging ideal collector as it attains the highest possible concentration of radiant energy permitted by the second law of thermodynamics [18]. The main advantages of CPCs over other solar collectors include high optical efficiency [18], minimum errors of alignment [19], elimination of the diurnal tracking requirement at intermediate concentrations (up to 10×) [18], and being able to collect both diffuse and direct radiation [18][19][20][21]. Generally, CPCs are categorised as two-dimensional (2D) [18,19,21] or three-dimensional (3D) collectors [18,19,22].…”
Section: Introductionmentioning
confidence: 99%
“…A cost-effective and improved CPV system is obtained by producing the same amount of power by using less number of cells compared to conventional number of cells. It is reported that a low concentration photovoltaic system (LCPV) can reduce the cost up to 40% compared to a simple flat PV system [2], [3]. Due to their potentials of non-tracking, high liability and low cost, a considerable amount of research has been done for the development of various types LCPV applications [4].…”
Section: Introductionmentioning
confidence: 99%